Good food manufacturing practices in the Covid-19 context - Ana Paula Garcia Fernandes dos Santos; Cilene Silva Ribeiro; Gabriela Moraes Fortuna (Universidade do Estado do Rio de Janeiro, 2021)
Introduction: After the start of the pandemic caused by the new coronavirus, the world was faced with the need for social isolation. All services not considered essential were instructed to remain indefinitelyclosed. In this scenario, food services were able to continue working, however, with a range of changes in their routines and good manufacturing practices. Objective: This study aimed to analyze the main changes that occurred in the good manufacturing practices of Food Units, after the beginning of the new coronavirus pandemic. Method: A qualitative study was carried out, with data production through online interviews with managers of Food Units. The questionnaire used was developed especially for this project, being divided into three stages: personal data, unit data and changes made due to the pandemic. Result: In total, the survey obtained 70 responses, from professionals who work in the city of Curitiba, PR. Among the actions most often mentioned, we highlight the acquisition of new protective equipment, reduction of cafeteria capacity and increase in the use of cleaning products and alcohol gel. Conclusion: The development of good practices and the implementation of additional safety measures can contribute to reducing the transmission of the new coronavirus, but it is essential that professionals adopt only measures based on current legislation and guidelines of the top health organizations, in order to avoid the dissemination of dubious and erroneous information.